The Pharmacokinetics of Beta-Lactam Antibiotics Using Scavenged Samples in Pediatric Intensive Care Patients: The EXPAT Kids Study Protocol - Schouwenburg, Stef; Wildschut, Enno D.; de Hoog, M.; Koch, Birgit C.P.; Abdulla, Alan (Frontiers in Pharmacology, 2021)
Background Emerging evidence supports the importance of optimized antibiotic exposure in pediatric intensive care unit (PICU) patients. Traditional antibiotic dosing is not designed for PICU patients, as the extreme pharmacokinetic (PK) behavior of drugs threatens the achievement of optimal antibiotic treatment outcomes. Scavenged sampling is a sampling strategy which may have positive implications for routine TDM and PK research, as well as monitoring other biomarkers. EXPAT Kids study was designed to analyze whether current empiric dosing regimens of frequently used beta-lactam antibiotics achieve defined therapeutic target concentrations in PICU patients. Methods A mono-centre, exploratory pharmacokinetic and pharmacodynamic study was designed to assess target attainment of beta-lactam antibiotics. One hundred forty patients will be included within 24 months after start of inclusion. Based on optimal sampling, at various time points serum concentration of the study antibiotic (cefotaxime, ceftazidime, ceftriaxone, cefuroxime, flucloxacillin, and meropenem) are determined. In parallel with these sampling moments, residual material is collected to validate the use of blood of scavenged heparinized astrup syringes for the quantification of antibiotic exposure. The primary outcome is the time that the free (unbound) concentration of the study antibiotic remains above one to four the minimal inhibitory concentration during a dosing interval (100%ƒT>MIC and 100%ƒT>4xMIC). Other included outcomes are disease severity, safety, length of stay, and inflammatory biomarkers. Discussion Potentially, scavenged sampling may enrich the EXPAT Kids dataset, and reduce additional blood sampling and workload for clinical personnel. The findings from the EXPAT Kids study will lead to new insights in the PK parameters of beta-lactams and consecutive effects on target attainment and clinical outcomes. Is there a need for more precision in dosing?